THE CORRELATION BETWEEN STUDENTS’ SELF-EFFICACY AND THEIR WRITING ABILITY AT SMKN 4 PEKANBARU - Pranindya Ayu Syahrani; Novitri Novitri; Rumiri Aruan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The main purpose of this study was to investigate the potential existence of a statistically significant relationship between students' self-efficacy and their Writing Ability at SMKN 4 Pekanbaru. The study utilized a quantitative methodology and employed a correlational research design. The study encompassed a population of 413 second-grade students at SMKN 4 Pekanbaru. A sample size of 35 pupils was selected using a cluster random sampling technique. The research utilized a questionnaire to assess students' academic self-efficacy and a writing recall text to evaluate their writing ability. In order to do data analysis, the researcher applied SPSS 25. The results demonstrated that the correlation coefficient between the two variables is 0,-113, indicating a no relationship. Furthermore, the determinant coefficient of students' academic self-efficacy is 1.28%. Based on the analysis, it can be deduced that there exists a somewhat insignificant and negative correlation between the two variables.Key Words: Correlation, Self-efficacy, Writing ability